Beyond the dopamine hypothesis of schizophrenia to three neural networks of psychosis: dopamine, serotonin, and glutamate - Stahl, Stephen M. (CNS spectrums, 2018)
Psychosis is now widely hypothesized to involve neural networks beyond the classical dopaminergic mesolimbic pathway, including serotonin and glutamate systems as well.Psychosis is now widely hypothesized to involve neural networks beyond the classical dopaminergic mesolimbic pathway, including serotonin and glutamate systems as well.